Improvement Of A New Analysis Technique Of Phenomenon Of Bulling And Cyberbullying Among Students At Different Stages - et. al., Ayat Abdel Khaleq Kamel , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, we have witnessed a number of technological breakthroughs. These developments affected young people in particular, who reaped many benefits from the Internet and mobile phones - such as access to educational materials, tools and interactive learning networks, establishing and maintaining peer relationships and friendships, and a creative outlet and civic engagement and self-discovery. However, there were threats and risks associated with the growth of the "virtual" environment. Cyberbullying is one of the most common threats young people face online, and it is more likely to come from someone they know than from a stranger. A thorough investigation of cyberbullying and bullying was also conducted using questionnaire and analysed using statistical software programs. Anyone can become a target of bullying, so there is no point in blaming themselves and looking for the causes, as acts of bullying do not necessarily end even if the targeted people try to change themselves according to what the bully demands.